2006
DOI: 10.1159/000096403
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Time and Ultrafiltration Rate Are More Important in Dialysis Prescription than Small Molecule Clearance

Abstract: Chronic hemodialysis sessions, as developed in Seattle in the 1960s, were long procedures with minimal intra- and interdialytic symptoms. Over the next three decades, dialysis duration was shorten to 4, 3, even 2 h in thrice weekly schedules. This method spread rapidly, particularly in the United States, after the National Cooperative Dialysis Study suggested that the time of dialysis is of minor importance as long as urea clearance multiplied by dialysis time and scaled to total body water (Kt/Vurea Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 114 publications
1
26
0
Order By: Relevance
“…Though this group was a small proportion of our total cohort (<1%), they also had a relatively long treatment time with a median of 4.0 h per session, further adding to the notion that long treatment time may improve patient outcomes. Twardowski [26] stressed the importance of treatment time and UFR rather than small molecular clearance (Kt/V urea ) in assessing dialysis quality. In our study, associations between UFR and mortality were similar across strata of single-pool Kt/V.…”
Section: Discussionmentioning
confidence: 99%
“…Though this group was a small proportion of our total cohort (<1%), they also had a relatively long treatment time with a median of 4.0 h per session, further adding to the notion that long treatment time may improve patient outcomes. Twardowski [26] stressed the importance of treatment time and UFR rather than small molecular clearance (Kt/V urea ) in assessing dialysis quality. In our study, associations between UFR and mortality were similar across strata of single-pool Kt/V.…”
Section: Discussionmentioning
confidence: 99%
“…Shortening the procedure to tailor dialysis to a minimum Kt/V may provoke intradialytic symptoms, postdialysis fatigue, and nonadherence to therapy; thus, this is not recommended. 124 Normotension can be achieved independently of the duration of dialysis if the control of volume is adequate. 125 In fact, left ventricular mass index was also improved to a comparable degree in DRIP trial participants, in which the duration of dialysis was not altered but the dry weight was challenged.…”
Section: Frequent Dialysis and Its Effect On Bpmentioning
confidence: 99%
“…Indeed, patient survival is often better in Asian PD patients, despite a Kt/V of only 1.7 [24] . It is also argued that Kt/V is a poor measure of dialysis quality [25] . We have shown that a dietary intake of less than 1.2 g/kg/day of protein does not necessarily lead to malnutrition in Asian dialysis patients [26] .…”
Section: Discussionmentioning
confidence: 99%
“…There are many factors affecting HD and PD efficiency [28] . Kt/V remains the most accepted index used to assess small-solute clearance in HD and CAPD even though it is believed that smallmolecule clearance is not so important in dialysis prescription [25] . Urea kinetic modeling provides a way to quantitatively examine the relationship between dialysis dose and accumulation as well as removal of uremic toxins.…”
Section: Discussionmentioning
confidence: 99%